2020
DOI: 10.3390/agronomy10060908
|View full text |Cite
|
Sign up to set email alerts
|

Different Ground Vegetation Cover Management Systems to Manage Cynodon dactylon in an Irrigated Vineyard

Abstract: Ground cover management in vineyards in Spain is focused on minimizing soil erosion and compaction. Such practices have influenced the weed community structure in the inter-rows, contributing to the spread of the high noxious weed Cynodon dactylon (L.) Pers. This fact highlights the need for further investigation of the interaction between ground cover practices and weed control techniques. In this study, the effect of four different ground cover managements (M) in the inter-rows on C. dactylon population dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 36 publications
(47 reference statements)
1
21
1
Order By: Relevance
“…However, this last method (tillage) also favors the presence of C. arvensis , as Abad et al [ 52 ] reported. Conversely, Ormeño-Núñez et al [ 53 ] observed an 82% reduction in the dry matter of Cynodon dactylon (another problematic rhizomatous weed species) in Secale cereale mulch, compared with chemical plus mechanical control, while Valencia-Gredilla et al [ 54 ] observed that inter-row tilling and a H. vulgare cover crop mulched in autumn was effective in maintaining low levels of C. dactylon in the inter-row zone. In our study, C. dactylon did not show any preference for mulch or tillage treatments ( Figure 7 ); nevertheless, this species was capable of overcoming the physical barrier of mulches and developed on top of them, probably due to its vegetative propagation thorough rhizomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, this last method (tillage) also favors the presence of C. arvensis , as Abad et al [ 52 ] reported. Conversely, Ormeño-Núñez et al [ 53 ] observed an 82% reduction in the dry matter of Cynodon dactylon (another problematic rhizomatous weed species) in Secale cereale mulch, compared with chemical plus mechanical control, while Valencia-Gredilla et al [ 54 ] observed that inter-row tilling and a H. vulgare cover crop mulched in autumn was effective in maintaining low levels of C. dactylon in the inter-row zone. In our study, C. dactylon did not show any preference for mulch or tillage treatments ( Figure 7 ); nevertheless, this species was capable of overcoming the physical barrier of mulches and developed on top of them, probably due to its vegetative propagation thorough rhizomes.…”
Section: Discussionmentioning
confidence: 99%
“…All of them are capable of clonal growth through rhizome production and fragmentation, particularly tubers in purple nutsedge. Populations of C. rotundus mainly affect vegetable crops [17], those of C. dactylon are very persistent in fruit orchards and vineyards [19], S. halepense is a troublesome weed species in orchards and in maize fields [20], and P. dilatatum is very persistent in lawns and in other perennial crops [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, in Mediterranean climates where vineyard-producing areas are generally associated with a scarcity of water resources, their use is still very unusual [ 40 ] and plant covers, if any, are commonly limited to the vineyard inter-rows. Nonetheless, combining under-vine living mulches with irrigation application could be a suitable strategy, as plant covers, besides improving soil conditions and water infiltration, could also limit the presence of noxious weed species [ 7 , 41 ]; while irrigation application could reduce the negative impact of water competition due to plant covers on the vineyard [ 42 ]. Therefore, such competition between cover crops and grapevines must be carefully managed to avoid undesirable results in grape production and quality [ 43 ].…”
Section: Introductionmentioning
confidence: 99%